Reality of a Sustainable Economy - Miron Dumitrescu; Paula – Angela Vidrascu; Mihaela Daniela Niculescu; Serban Taranu (Hyperion Economic Journal, 2013)
Sustainable development addresses the complex concept of quality of life, economically, socially and environmentally, by promoting the idea of balance between economic development, social equity, efficiency and environmental conservation. This article aims to analyze a number of indicators of sustainable development by establishing specific passage to a reasonable and realistic development model generating high added value, interest in knowledge and innovation in order to continuously improve the quality of people's lives and their realities as well as the harmony with the natural environment